Potential demand for civet coffee in Davao City - Lacandula, Joyce S.
This study was conducted with a view to determining the potential demand for Civet coffee in Davao City. The analysis utilized mainly primary data, which were gathered through in-person interview from coffee consumers of five selected coffee shops in Davao City: two of the coffee shops were serving civet coffee. Regression analysis was utilized to determine willingness to pay for civet coffee. Results show that majority of the consumers had heard about civet coffee, mostly from friends and acquaintances. Also, majority of the respondents were willing to try civet coffee. But those were willing to try were mostly those who were less than 35 years old, those who were single, and those in the higher income bracket. the regression analysis revealed that for all income groups, awareness about civet coffee and willingness to try the product were statistically significant in determining willingness to pay; both had positive relationship with WTP. Income, on the other hand was statistically significant in determining WTP only of the highest and lowest income groups. For the highest income group, there was a positive relationship between income and WTP; the relationship was negative for the lowest income group. The results indicate that indeed, there is potential demand for civet coffee in Davao City. Since the product appeared marketable to the higher income group, marketing strategies should be directed more to this group.